Can restoration of the commons foster resilience? A quasi-experimental comparison of COVID-19 coping strategies among rural households in three Indian states - Hughes, Karl; Priyadarshini, Pratiti; Sharma, Himani; Lissah, Sanoop; Chorran, Tenzin; Meinzen-Dick, Ruth S.; Dogra, Atul; Cook, Nathan; Andersson, Krister (International Food Policy Research Institute, 2021)
India has been hard hit by the COVID-19 pandemic. In the context of a larger quasi-experimental impact assessment, we assess the pandemic’s effects on coping behavior in 80 villages spread across four districts and three states (n=772). Half of these villages were targeted by a largescale common land restoration program spearheaded by an NGO, the Foundation for Ecological Security (FES). The other half are yet to be targeted but are statistically similar vis-à-vis FES’s village targeting criteria. Analyzing the results of a phone survey conducting eight to ten months into the pandemic and its associated lockdowns, we find that the livelihood activities of households in both sets of villages were adversely impacted by COVID-19. Consequently, most households had to resort to various coping strategies, e.g., distressed asset sales and reduced farm input expenditure. From the same mobile survey data, we further construct a Livelihoods Coping Strategies Index (LCSI) and find that households in villages targeted by FES’s common land restoration initiative score 11.3% lower on this index on average. While modest, this statistically significant effect estimate (p<0.05) is consistent across the four districts and robust to alterative model and outcome specifications. We find no empirical support that our observed effect was due to improved access to common pool resources or government social programs. Instead, we speculate that this effect may be driven by institutional factors, rather than economic, a proposition we will test in future work.